Study on the novel binder based biodegradable polyhyroxyalkanoates (PHA) for metal injection moulding application - Hassan, Norita (2018)
Development of biopolymer binder for metal injection molding (MIM) feedstock play an important roles in improvising the debinding step in MIM process as it is the most time consuming step in the process. The backbone binder used in the industry is petroleum based polymer binder with high debinding time where this condition promotes defect formation to the part along the process. Replacing petroleum based polymer with polyydroxyalkanoates (PHA) biopolymer as the binder is one of idea to reduce the debinding time which reduce the processing cost as well as the formation of defects or failures to the injected part. Therefore, current research was done to provide reliable data on backbone binder mechanical strength, rheological properties of the feedstock and debinding behavior to determine the compatibility of PHA as backbone binder for MIM. The experimental work was divided into 4 main parts, development of backbone binder, rheological study of binder, debinding behavior of the binder and sintering of injected part. First, PHA was plasticized with different composition 1wt% to 5wt% of EPO and tensile tested. The best plasticized PHA was selected for backboned binder application, the binder system used was paraffin wax (PW), plasticized PHA and stearic acid (SA) with ratio 60:30:10 respectively. The second part was done by preparing four feedstock with different powder loading 70vol%, 71vol%, 72vol% and 73vol% and theologically tested. The optimum composition was injected and solvent debound in heptane at 40°C, 50°C and 60°C for 6 hours. The weight loss was measured and analyzed. Next, thermal debinding was set at 500°C with 4 different heating rate 2, 4, 6 and 8°C/min in vacuum atmosphere for 1 hour. The brown part was analyzed optically. The defect free brown part was sintered at 1380°C with heating rate 5°C/min for 3 hours. The density, hardness, shrinkage percentage and microstructure of sintered part was measured and observed. Based on the tensile test, plasticized PHA with 3wt% EPO exhibit high Young’s modulus and the most suitable for backbone binder application. It was found that feedstock with 71vol% powder loading was the optimum composition. The optimum condition for solvent debinding in heptane were at 60°C for 60 minutes with 100% of the soluble binder was removed. This finding proved that new binder system reduced the debinding time. Through the experiment, it is found that defect was formed on the green part that thermally rebound. However, for grey parts no defect was formed for all heating rate. The sintered part shows insignificant different of all the properties between the samples, hence it can be conclude that debinding parameter has no significant to the sintered part. The value for density, shrinkage percentage and macro hardness of sintered part was 7.22g/cm3, 6.2% and 67.2 HRB. Thus, it is found that PHA can replace the petroleum based polymer as a backbone binder. However some improvement need to be done on the sintering condition to obtain optimum properties of SS316L MIM sintered part.